Cryogenic turning of in-house cast magnesium based MMCs: A comprehensive investigation - Navneet Khanna; Narendra M. Suri; Prassan Shah; Hussien Hegab; Mozammel Mia (Journal of Materials Research and Technology, 2020)
To increase fuel efficiency, the demand for materials having high specific strength is increasing in automotive and aerospace industry. In this context, a tailor-made AXZ911/10SiC Metal Matrix Composites (MMCs) is developed. The characterization of in-house cast AXZ911/10SiC is done meticulously through SEM microscopy, EDS and XRD analysis. The machining performance of AXZ911/10SiC MMCs is compared for dry and indigenously developed sustainable cryogenic machining techniques. The full factorial method is employed to investigate the impact of process parameters and environmentally clean cutting fluid strategies (dry, cryogenic with LCO2 and LN2) on machining performance indicators viz. cutting force, power consumption and surface roughness. In aggregate, 17.40% and 2.93% lower cutting force while 48.55% and 36.61% lower power consumption are observed with LN2 as cryogenic fluid as compared to dry and cryogenic fluid with LCO2 individually. Including all turning tests, the 33.93% and 36.20% lower surface roughness are observed in dry condition as compared with cryogenic fluid with LN2 and LCO2 respectively. A separate sustainability model is developed based on environmental impact, machining cost, and power consumption and validated at each cutting condition for cutting force and surface roughness.